Biliary Atresia Is Associated With Hypertension. Issue 2 (August 2015) - Matloff, Robyn G.; Diamond, Rebekah; Weinberg, Alan; Arnon, Ronen; Saland, Jeffrey M.
Abstract Objectives: The improved survival of pediatric liver transplant recipients is accompanied by an increase in long-term comorbidities. A recently highlighted concern, hypertension, is associated with chronic kidney disease (CKD) in this population and can result in other target-organ damage during childhood. The prevalence of hypertension in pediatric liver transplantation is imprecisely known. In addition, individual etiologies of liver failure may convey different risks of hypertension. We sought to study the effect of liver transplantation on the prevalence of hypertension and CKD in patients with biliary atresia (BA). Methods: We conducted a retrospective chart review of 160 patients with BA followed at the Mount Sinai Medical Center, New York, from 1987 to 2012. Data were accumulated from the initial and subsequent visits at approximately 6 months, 1, 3, 5, 10, and 15 years of age. Hypertension was defined as systolic blood pressure >95th percentile for age, sex, height, and/or use of antihypertensive medication. Renal function was examined over time. Data were stratified by liver transplantation status at the time of visit. Results: A high prevalence of hypertension was observed from the initial visit through age 10, independent of transplant status (transplanted: 48% initial visit and 13% after 10 years vs nontransplanted: 55% initial visit and 17% after 10 years [P = ns for transplant status]). Mean estimated glomerular filtration rate (eGFR) was lower among liver transplant patients as compared with nontransplant patients and declined posttransplant. The incidence of CKD was higher among transplant patients. Conclusions: Hypertension is common among children with BA, independent of liver transplant status. Transplant patients had significantly reduced renal function, which continued to decline over time. Hypertension was not associated with reduced eGFR.